Drought, livestock holding, and milk production: A difference-in-differences analysis - Meseret B. Abebe; Yonas Alem (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Climate change is making El Ni\~nos more frequent and intense. Therefore, understanding the effects of El-Ni\~no-induced climatic events is essential to designing effective coping and adaptation strategies. We identify the impact of the 2015-16 El-Ni\~no-induced large-scale drought on smallholder farmers' livestock holding and milk production using nationally representative data collected before and after the drought. We show that drought reduced milk production and livestock holding by 25.8% and 8.4%, respectively. Heterogenous impact analysis suggests that asset-rich households sold livestock and financed feed purchases, which insulated their milk production from the drought. In contrast, asset-poor households kept their livestock despite the severe drought and absorbed all the decline in milk production. Our findings have important implications for formulating safety net and adaptation programs targeting smallholder farmers and the livestock sector in a rapidly changing climate. – – Durch den Klimawandel werden El Ni\~nos immer häufiger und intensiver. Es ist wichtig, die Auswirkungen der El-Ni\~no-Ereignisse zu verstehen, um wirksame Bewältigungs- und Anpassungsstrategien zu entwickeln. Wir ermitteln die Auswirkungen der durch El Ni\~no verursachten großen Dürre 2015-16 auf den Viehbestand und die Milchproduktion von Kleinbauern anhand national repräsentativer Daten, die vor und nach der Dürre erhoben wurden. Wir zeigen, dass die Dürre die Milchproduktion und den Viehbestand um 25,8 % bzw. 8,4 % verringerte. Die Analyse der heterogenen Auswirkungen zeigt, dass vermögensstarke Haushalte ihren Viehbestand verkauften und damit den Kauf von Futtermitteln finanzierten, was ihre Milchproduktion Milchproduktion vor der Dürre schützte. Im Gegensatz dazu behielten die vermögensarmen Haushalte ihren Viehbestand trotz der schweren Dürre bei und fingen den gesamten Rückgang der Milchproduktion auf. Unsere Ergebnisse haben wichtige Implikationen für die Formulierung von Sicherheitsnetz- und Anpassungsprogrammen für Kleinbauern und den Viehzuchtsektor in einem sich rasch verändernden Klima.
Keywords: D13; O13; O44; Q18; Q54; 330; Drought; diff-in-diff; climate change; smallholder farmer; livestock holding